Frequency of Genetic Testing Among Patients With Epithelial Ovarian, Fallopian Tube, and Peritoneal Cancers: A Strategy to Improve Compliance - Jude Nawlo; Kevin Espino; Deanna Gerber; Meredith Akerman; Kent Chan; Edward Jimenez; Eva Chalas (International Journal of Genomics)
Conclusion: Internal policy developed based on analysis of compliance with the SGO position statement and subsequent implementation of POC testing led to a significant increase in GT, indicating improvement in quality medical care. GT rates in this population are markedly higher than reported in the literature.